Molecular ecology and hierarchical models elucidate chronic wasting disease dynamics - Galloway, Nathan L., author; Antolin, Michael F., advisor; Hobbs, N. Thompson, committee member; Miller, Michael W., committee member; Huyvaert, Kathryn P., committee member (Colorado State University. Libraries, 2018)
Prions present a unique evolutionary scenario because a single gene codes for both a disease agent and a functionally constrained native protein. The prion precursor gene, Prnp, codes for the prion precursor protein, PrP, which is constitutively expressed as a native isoform within all mammals. Upon misfolding to the disease isoform, known as prions, the same protein causes fatal neurodegenerative diseases known as transmissible spongiform encephalopathies. We review the literature and available data for the genetics of Prnp in order to examine its molecular evolutionaryhistory, and the likely force of natural selection acting on it, by analyzing genetic diversity both within and between species within Class Mammalia. We accessed Prnp nucleotide sequences of a large number of mammalian species from GenBank. We undertook three distinct analyses of these molecular data to characterize the force of selection acting on Prnp through comparisons of gene sequences and allele frequencies within and between species. Our analyses include: 1.) comparisons of genetic and amino acid polymorphisms across protein domains within Prnp, 2.) a within and between species comparison of nucleotide diversity within Prnp to characterize natural selection acting on the gene, and 3.) observed frequencies of genetic and amino acid polymorphisms from natural populations of animals. We show that amino acid substitutions reported to correlate with prion disease risk within species do not aggregate within particular protein structural domains, but rather are disparately located throughout. Branch model estimates using Phylogenetic Analysis by Maximum Likelihood across mammals show that Prnp undergoes strong purifying selection at the broad scale, that purifying selection is stronger between species than it is within species but no evidence that species orally susceptible to prion disease experience unique positive selection. We do show, however, that amino acid substitutions occur at higher frequencies than synonymous substitutions within Prnp, in direct conflict with the expectations for purifying selection. This evidence suggests that Prnp is experiencing balancing selection in opposition to the purifying selection observed at the large scale; this unique selective pressure may be due to the presence of prion disease. Ecological processes such as reproduction, habitat use, and disease epizootiology contribute to the growth or decline of wildlife populations, but many of these processes go directly unobserved. We set out to describe gene flow and disease transmission to better understand the ecological role of chronic wasting disease (CWD) in a northern Colorado population of mule deer (Odocoileus hemionus). CWD, a fatal prion disease, has been affecting this population for many decades. It has not caused extirpation of the deer, but may play an important limiting role in population growth and resilience. We employed genetic methods to analyze neutral genetic markers, which provide information about gene flow. Further, we examined allelic variation in the functional prion precursor gene, Prnp, which codes for the disease-causative prion of CWD and has alternative alleles with one (225F) that confers some resistance to prion disease within individual deer. The study in northern Colorado included sampling across four winter ranges. Genetic analysis identified four genetic lineages of deer, but lineages were distributed throughout the study area and did not correspond with winter ranges used annually with high fidelity by groups of females. Further, we show that males drive gene flow across genetic lineages. In contrast, CWD prevalence was spatially segregated: CWD-positive female deer were located in two of the winter ranges and absent from the others. This suggests that neither breeding sites nor natal dispersal are the primary means of disease spread in females across the winter ranges. Furthermore, we found, as previously reported, that an individual deer's Prnp genotype predicts the likelihood of a positive disease test. Even so, the frequency of the Prnp 225F allele was similar across winter ranges, and was notably higher than that reported in neighboring populations a decade earlier. Thus, it appears that gene flow spreads the favored allele across the study area despite different selective regimes in winter ranges. Our work shows the benefit of using population genetics to gain insight into ecological processes that go directly unobserved, such as the epizootiology of chronic wasting disease. Chronic wasting disease is a fatal neurodegenerative prion disease that infects members of the deer family in North America and Scandinavia. We conducted a five-year mark recapture study of a northern Colorado population of mule deer (Odocoileus hemionus) with endemic disease, including 217 females. All study animals were also genotyped at the prion precursor gene, Prnp, which has alternative alleles in many species to express amino acid differences that alter prion disease dynamics. Mark-recapture analysis revealed decreased disease incidence for individuals expressing genotypes with at least one copy of the minor allele, including heterozygotes, Prnp 225SF (expressing both a serine and phenylalanine at amino acid position 225) , and rare homozygotes, 225FF.We found no evidence for an evolutionary trade-off of decreased survival of CWD-negative deer for this group but emphasize the difficulty in estimating dynamic rates for the rare homozygotes alone. We employed estimates of annual disease risk and survival from this study as well as recruitment estimates from the literature, to forecast the expected future minor allele frequency in the population under the observed disease risk. This forecast revealed a clear expected evolutionary increase in the Prnp minor allele (225F) frequency given our model and field data.